Improvement of Productivity, Agro-Meteorological Indices, Energetics and Nutrient Balance of Rice-Groundnut Cropping System (Bangladesh Journal of Botany, 2022)
Effects of two rice establishment methods namely, direct seeding (DSR) and transplanting (TPR) and three nutrient management practices in rice and three nutrient management practices in groundnut of rice (Oryza sativa L.)- groundnut (Arachis hypogaea L.) system were investigated. TPR produced 7.1 and 5.6% higher grain (5.75 t/ha) and straw (6.81 t/ha) yields than DSR with superior yield attributing characters. INM (green manuring + 50% STBN + 100% P2O5 + 100% K2O) enhanced grain and straw yields of rice by 13.3 and 10.0% over inorganic (100% STBF) and by 15.2 and 8.2% over organic (green manuring + 1/3rd STBN through vermicompost + 1/3rd STBN through neem oil cake) management practices, respectively. INM practice in groundnut (75% STBN + 25% STBN (FYM) + lime 0.2 LR + biofertilizers (Rhizobium + PSB) + 100% P2O5 + 100% K2O) also produced the highest pod (2.74 t/ha) and haulm (3.62 t/ha) yield, which were, respectively, 39.8 and 5.5% higher over 75% STBF and 20.2 and 1.4% more than 100% STBF. But, DSR resulted in higher system yield (12.7 t REY/ha), system productivity (34.7 kg REY/ha/day), energy productivity and accumulated heat use efficiency than TPR system. INM practice in rice showed maximum system yield, productivity and P and K balance whereas, organic approach resulted in higher N balance. INM in groundnut produced the maximum system yield, productivity, HUE and N balance, but 75% STBF showed maximum agro-meteorological indices, P and K balance in spite of lowest system yield and system productivity. Energy productivity and efficiency were higher with 100% STBF in groundnut.Bangladesh J. Bot. 51(3): 477-486, 2022 (September)